Parametric Audio Based Decoder and Music Synthesizer for Mobile Applications - SZCZERBA, Marek; OOMEN, Werner; THERSSEN, Dieter (Archives of Acoustics, 2011)
This paper reviews parametric audio coders and discusses novel technologies introducedin a low-complexity, low-power consumption audio decoder and music synthesizerplatform developed by the authors. The decoder uses parametric codingscheme based on the MPEG-4 Parametric Audio standard. In order to keep thecomplexity low, most of the processing is performed in the parametric domain. Thisparametric processing includes pitch and tempo shifting, volume adjustment, selectionof psychoacoustically relevant components for synthesis and stereo imagecreation. The decoder allows for good quality 44.1 kHz stereo audio streaming at24 kbps. The synthesizer matches the audio quality of industry-standard samplebasedsynthesizers while using a twenty times smaller memory footprint soundbank.The presented decoder/synthesizer is designed for low-power mobile platforms andsupports music streaming, ringtone synthesis, gaming and remixing applications.